What's next? Some priorities for young planning scholars to tackle tomorrow's complex challenges - Husar, Sila Ceren Varis; Mehan, Asma; Erkan, Rueya; Gall, Tjark; Allkja, Ledio; Husar, Milan; Hendawy, Mennatullah (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Many European planning schools recently celebrated their 50th anniversary: a sign that planning education became a distinct and established discipline in Europe. Simultaneously, political regimes, paradigms, cultures, and economies continue fuelling mixed connotations within the planning sector. Additionally, growing wicked problems in built areas emphasize an even greater need for well-trained planners. These challenges span climate crises, wars, authoritarian regimes, socio-political instability, and constantly changing global geopolitics. The increasingly complex demands on planners are highly pertinent for Young Academics (YA). They require political, regulatory, and technical knowledge to navigate the profession. To support them and represent their voices in planning debates, the YA network (YAN) of AESOP was established in 2003. We, the current Coordination Team, use this paper to voice our take on the question of what planning challenges dominate and what can be done to prepare YAs better for the future. Building on plenty discussions within the YAN, literature, and AESOP's activities at large, we propose: A challenge compilation for the profession, a list of core capacities, and a framework for future education. This shall aid in enabling YAs and educators today to set the foundation for planning sustainable and people-centered settlements tomorrow.
Keywords: Planning; planning education; complexity; European planning; AESOP; INTERDISCIPLINARY; TRANSDISCIPLINARITY; Environmental Sciences & Ecology; Geography; Public Administration; Urban Studies